An Exploration of Anxiety towards English for Specific Purposes (ESP) - Pratika Ayuningtyas (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2020)
This study aims at exploring the Foreign Language Anxiety among the ESP Students. The participants in this study were183 students of three different departments of Politeknik Sawunggalih Aji, Indonesia. There were 56 students of Information Technology Department, 93 students of Accounting Department and 34 students of Business Administration Department. The Foreign Language Anxiety Scale (FLCAS) (Horwitz, Howitz & Cope, 1986) was used to collect the data. The general level of anxiety among students of Politeknik Sawunggalih Aji, Indonesia is average to high as their mean score is 81.84. There are 169 students who suffered from average to high anxiety or 92.34%.Â The results of the analysis revealed that the students of Information Technology department experienced the highest level of anxiety with the mean score of 84.8; the students of Accounting department experienced the next higher level of anxiety with the mean score of 80,8 and the students of Business Administration department experienced the lowest of anxiety with the mean score of 79,8%. Knowing these results, teachers should provide the materials and the teaching method which can help students overcoming their anxiety towards English. Therefore the level of anxiety can be pressed to low.